Let's Avoid Destructive Ideas! - Sidikmetov Kudratulla (Penerbit Jurnal Indonesia, 2024)
This article states that Islam is a religion of peace. The value of peace in Islam is justified by verses and hadiths. Disruptive ideas are refuted. The topic will be covered in more detail with real life examples. The evidence is from reliable sources.